Variability in Airs-Retrieved Cloud Amount and Thermodynamic Phase over West Versus East Antarctica Influenced by the Sam - Rowe, P (Blackwell Publishing Ltd, 2015)
In a sample of summertime cloud retrievals from the NASA Atmospheric Infrared Sounder (AIRS), a positive Southern Annular Mode (SAM) index polarity is associated with greater cloud frequency and larger effective cloud fraction over West Antarctica compared with a negative SAM index polarity. The opposite result appears over the high East Antarctic Plateau. Comparing AIRS-retrieved cloud fraction with Antarctic Automatic Weather Station 2m air temperature data, a positive and significant correlation is found over most of West Antarctica, signifying a longwave heating effect of clouds. Over East Antarctica correlations between Sun elevation and 2m air temperature are strongest, consistent with lower cloud amount. ©2015. American Geophysical Union. All Rights Reserved.